Perencanaan Konfigurasi Layout Slipway Untuk Meningkatkan Kapasitas Winch Pada Galangan X - Muhammad Irzam Amrizal; Adi Wirawan Husodo; Heroe Poernomo (Proceedings Conference on Marine Engineering and its Application, 2023)
This research the planning of slipway layout configuration to increase the capacityof the existing winch at the shipyard. The slipway layout configuration includes several thingssuch as slipway layout, number of Pulleys turns, Pulley position, and ground conditions. Thisresearch aims to determine the maximum safe working load value of wire rope, the pullingforce of each ship that will be docking, and the appropriate number of turns on the Pulley. Theship variations used to plan the slipway layout configuration are 10813 DWT container ship,8200 DWT container ship and 7080 DWT cargo ship. Variations are made to determine thenumber of Pulley requirements and Pulley windings for each ship that will be docked. Themaximum force calculation results show that the 10813 DWT container ship requires 13 Pulleywindings. while the 8200 DWT container ship requires 11 Pulley windings. The 7080 DWTship requires 9 Pulley windings. In planning the slipway layout configuration to increase thewinch capacity, 1 Pulley is added to the fixed pulley and 1 Pulley to the moving Pulley so that13 turns are obtained.